2014
DOI: 10.3201/eid2010.131680
|View full text |Cite
|
Sign up to set email alerts
|

Human Granulocytic Anaplasmosis, South Korea, 2013

Abstract: We report a patient with human granulocytic anaplasmosis in South Korea. The patient had fever and thrombocytopenia. Human granulocytic anaplasmosis was confirmed by seroconversion, PCR, and sequence analysis for Anaplasma phagocytophilum. Morulae were observed in the cultured HL-60 cells inoculated with blood from the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 13 publications
(12 reference statements)
3
61
1
Order By: Relevance
“…Phylogenetic trees comparing the five human A. phagocytophilum strains in this study with various strains from Korea and other countries are shown in Figure 1. In comparison with the Korean strains ( Figure 1A), the five strains in this study were not identical, but closely related to each other and to the first human isolate in Korea (Korea/Gangwon/2013, KF805344) 21 ; a group of strains, which included two of the three KWD strains that were relatively distant from the five strains of this study, were also noted ( Figure 1A). In comparison with the strains from other countries, the five strains of this study were close to a human isolate from the United States and were relatively distant from the five strains from China, Japan, and Italy, which included two of the three deer isolates and a muntjac isolate ( Figure 1B).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Phylogenetic trees comparing the five human A. phagocytophilum strains in this study with various strains from Korea and other countries are shown in Figure 1. In comparison with the Korean strains ( Figure 1A), the five strains in this study were not identical, but closely related to each other and to the first human isolate in Korea (Korea/Gangwon/2013, KF805344) 21 ; a group of strains, which included two of the three KWD strains that were relatively distant from the five strains of this study, were also noted ( Figure 1A). In comparison with the strains from other countries, the five strains of this study were close to a human isolate from the United States and were relatively distant from the five strains from China, Japan, and Italy, which included two of the three deer isolates and a muntjac isolate ( Figure 1B).…”
Section: Resultsmentioning
confidence: 62%
“…HGA cases have been reported in China, 13 Japan, 14 and Korea, 21 but few retrospective cases have been reported in Asia. Among 70 febrile patients, five HGA cases were confirmed over a 10-year period at a hospital in Busan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case of HGA was recently reported in Korea (Kim et al 2014). Although there is no evidence of transmission from animals to humans, A. phagocytophilum is transmitted to horses and humans by the same tick species.…”
Section: Discussionmentioning
confidence: 99%
“…Several Korean studies have reported the presence of A. phagocytophilum in a variety of mammals, including rodents, dogs, and cattle (Chae et al 2008b;Jung et al 2012;Kang et al 2013), and a case of HGA has recently been documented in Korea (Kim et al 2014). In recent decades, there has been a gradual increase in temperatures worldwide due to global warming, and this climate change is expected to influence the abundance and distribution of ticks (Leger et al 2013).…”
mentioning
confidence: 99%